Futurizing” Smart Service: Implications for Service Researchers and Managers. - Wünderlich, Nancy; Heinonen, Kristina; Ostrom, Amy L; Patricio, Lia; Sousa, Rui; Voss, Chris; Lemmink, Jos (Journal of Services Marketing)
Purpose – The purpose of this paper is to craft a future research agenda to advance smart service research and practice. Smart services are delivered to or via intelligent objects that feature awareness and connectivity. For service researchers and managers, one of the most fascinating aspects of smart service provision is that the connected object is able to sense its own condition and its surroundings and thus allows for real-time data collection, continuous communication and interactive feedback. Design/methodology/approach – This article is based on discussions in the workshop on “Fresh perspectives on technology in service” at the International Network of Service Researchers on September 26, 2014 at CTF, Karlstad, Sweden. The paper summarizes the discussion on smart services, adds an extensive literature review, provides examples from business practice and develops a structured approach to new research avenues. Findings – We propose that smart services vary on their individual level of autonomous decision-making, visibility and embeddedness in objects and customer lives. Based on a discussion of these characteristics, we identify research avenues regarding the perception and nature of smart services, the adoption of smart services, the innovation through smart services as well as regarding the development of new business models. Originality/value – Smart services is a new emerging topic in service marketing research, their implications on organizations, customers and the service landscape have not been fully explored. We provide a fresh perspective on service research by characterizing relevant aspects of smart service that will stimulate fruitful future research and advance the understanding and practice of smart services.
Keywords: Connected services; Intelligent object; New service type; Smart services

Conducting Service Research that Matters. - Gustafsson, Anders; Aksoy, Lerzan; Brady, Michael K; McColl-Kennedy, Janet R; Sirianni, Nancy J; Witell, Lars; Wünderlich, Nancy (Journal of Services Marketing)
Purpose – The purpose of this paper is to encourage the reader to think differently about service-related issues and to strive to conduct service research that makes a transformational impact on individuals, organizations and society. The authors suggest that service researchers are in an excellent position to develop research that matters by making stronger connections with theory and elevating purely applied research to research that is higher in both practical relevance and methodological rigor. Design/methodology/approach – This paper takes a conceptual approach, connecting pertinent literature with new ideas highlighted in this special issue. Findings – This paper proposes that service researchers look beyond traditional service applications, take a multi-disciplinary approach to problem-solving and make greater strides towards connecting theory and practice. The authors propose a Model of Rigorous and Relevant Research, and call for fresh thinking across a wide range of research areas, including enhancing the customer experience, crafting innovation, integrating technology and measuring service outcomes. Originality/value – The originality of this essay lies in its focus on revitalizing the discussion on relevance and rigor as a path forward for service research. Additionally, this paper offers new insights on core management aspects of service provision that provide a solid platform for future work in service research.
Keywords: Relevance; Service technology; Service innovation; Customer experience; Rigor; Service outcomes

The Value of Self-Service: Long-Term Effects of Technology-Based Self-Service Usage on Customer Retention. - Scherer, Anne; Wünderlich, Nancy; Von Wangenheim, Florian (MIS Quarterly)
Advancements in information technology have changed the way customers experience a service encounter and their relationship with service providers. Especially technology-based self-service channels have found their way into the 21st century service economy. While research embraces these channels for their cost-efficiency, it has not examined whether a shift from personal to self-service affects customer–firm relationships. Drawing from the service-dominant logic and its central concept of value-in-context, we discuss customers’ value creation in self-service and personal service channels and examine the long-term impact of these channels on customer retention. Using longitudinal customer data, we investigate how the ratio of self-service versus personal service use influences customer defection over time. Our findings suggest that the ratio of self-service to personal service used affects customer defection in a U-shaped manner, with intermediate levels of both self-service and personal service use being associated with the lowest likelihood of defection. We also find that this effect mitigates over time. We conclude that firms should not shift customers toward self-service channels completely, especially not at the beginning of a relationship. Our study underlines the importance of understanding when and how self-service technologies create valuable customer experiences and stresses the notion of actively managing customers’ cocreation of value.
Keywords: customer defection; customer retention; e-service; longitudinal; Self-service; value-in-context

Advancing Research on Loyalty Programs: A Future Research Agenda. - Breugelmans, Els; Bijmolt, Tammo H A; Zhang, Jie; Basso, Leonardo J; Dorotic, Matilda; Kopalle, Praveen; Minnema, Alec; Mijnlieff, Willem Jan; Wünderlich, Nancy (Marketing Letters)
Despite the growing literature on loyalty program (LP) research, many questions remain underexplored. Driven by advancements in information technology, marketing analytics, and consumer interface platforms (e.g., mobile devices), there have been many recent developments in LP practices around the world. They impose new challenges and create exciting opportunities for future LP research. The main objective of this paper is to identify missing links in the literature and to craft a future research agenda to advance LP research and practice. Our discussion focuses on three key areas: (1) LP designs, (2) Assessment of LP performance, and (3) Emerging trends and the impact of new technologies. We highlight several gaps in the literature and outline research opportunities in each area.
Keywords: Loyalty programs; Loyalty program design; Loyalty program performance assessment; Emerging trends; Partnership loyalty programs; Customer relationship management

A vulnerability's lifetime - Glanz, Leonid; Schmidt, Sebastian; Wollny, Sebastian; Hermann, Ben (Proceedings of the 15th International Conference on Knowledge Technologies and Data-driven Business - i-KNOW '15)

Design your analysis: a case study on implementation reusability of data-flow functions - Lerch, Johannes; Hermann, Ben (Proceedings of the 4th ACM SIGPLAN International Workshop on State Of the Art in Program Analysis - SOAP 2015)

Getting to know you: towards a capability model for Java - Hermann, Ben; Reif, Michael; Eichberg, Michael; Mezini, Mira (Proceedings of the 2015 10th Joint Meeting on Foundations of Software Engineering - ESEC/FSE 2015)

Hidden truths in dead software paths - Eichberg, Michael; Hermann, Ben; Mezini, Mira; Glanz, Leonid (Proceedings of the 2015 10th Joint Meeting on Foundations of Software Engineering - ESEC/FSE 2015)

Model-driven UI Development Integrating HCI Patterns - Yigitbas, Enes; Mohrmann, Bastian; Sauer, Stefan (Proceedings of the 1st Workshop on Large-scale and Model-based Interactive Systems: Approaches and Challenges, LMIS 2015, co-located with 7th ACM SIGCHI Symposium on Engineering Interactive Computing Systems {(EICS} 2015), Duisburg, Germany, June 23, 2015.)

A Model-Based Framework for Multi-Adaptive Migratory User Interfaces - Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Human-Computer Interaction: Interaction Technologies - 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings, Part II)

Bilateral matching and bargaining games - Mikroökonomie, Lehrstuhl

First Steps towards a Tool Chain for Automatic Processing of Multimodal Corpora - Menke, Peter; Freigang, Farina; Kronenberg, Thomas; Klett, Sören; Bergmann, Kirsten (Journal of Multimodal Communication Studies)

Komplexe Selbstlernaufgabe (,WiWi-Studies') in der Eingangsphase wirtschaftswissenschaftlicher Bachelorstudiengänge. Einblicke in ein Design-Based Research-Projekt mit Studierendenbefragungen - Zoyke, A.; Kremer, H.-Hugo; Sampaio-Araujo, J. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Integrating Human-Centered and Model-Driven Methods in Agile UI Development - Fischer, Holger Gerhard; Yigitbas, Enes; Sauer, Stefan (Proceedings of 15th IFIP TC.13 International Conference on Human-Computer Interaction (INTERACT))

What does Vocational Mean? Exploring the Understanding of Vocational in Higher Education and Vocational Education - Kremer, H.-Hugo; Rüschen, E. (Crossing Boundaries in Vocational Education and Training: Innovative Concepts for the 21st Century. Conference Proceedings)

Qualitätsdimensionen für interaktive Systeme - Stand der Arbeiten UPA AK Qualitätsstandards - Fischer, Holger Gerhard; Polkehn, Knut; Geis, Thomas; Kluge, Oliver; Behrenbruch, Kay; Riedemann, Catharina (Mensch und Computer 2015 - Usability Professionals)

Gestaltung der Studieneingangsphase an einer wirtschaftswissenschaftlichen Fakultät - Kerbs, N.; Kremer, H.-Hugo; Rüschen, E.; Sampaio-Araujo, J.; Zoyke, A. (Das Hochschulwesen)

Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung: Das Forschungs- und Entwicklungsprojekt InBig - Beutner, Marc; Kremer, H.-Hugo; Kundisch, Heike; Rohde, S.; Zoyke, A. (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Überlegungen zur Modellierung der Bildungsarbeit im Rahmen von InBig - Kremer, H.-Hugo; Zoyke, A. (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Enwticklungsprojekt InBig)

Bildungsgangarbeit an Berufskollegs. Diskussionsbericht zur Bestandserhebung an den Pilot-Berufskollegs im Projekt InBig - Kranert, T.; Kremer, H.-Hugo; Zoyke, A. (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Mensch und Computer 2015 - Usability Professionals. Tagungsband

Grundstrukturen und Arbeitsbasis - Zur Entwicklung der Standortkonzepte - InBig als Forschungsfrage und Entwicklungsarena - Kremer, H.-Hugo; Beutner, Marc; Kranert, T. (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kurzportrait zum Standortkonzept des Robert-Bosch-Berufskolleg der Stadt Dortmund - Rose, S.; Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kurzportrait zum Standortkonzept des Berufskollegs Ernährung, Sozialwesen, Technik in Geilenkirchen - Beutner, Marc; Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

,Voraussetzungen und Möglichkeiten der Gestaltung gemeinsamen Lernens für Jugendliche mit sonderpädagogischem Förderbedarf im Bereich Lern- und Entwicklungsstörungen' im Auftrag des Ministeriums für Schule und Weiterbildung des Landes Nordrhein-Westfalen - Kremer, H.-Hugo; Kückmann, Marie-Ann; Sloane, Peter F. E.; Zoyke, A.

Praxisformate in der Ausbildungsvorbereitung - Beutner, Marc; Eickhoff, A.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kollegiale Weiterbildung. Entwicklung, Qualifizierung und Rollenverschärfung für Nachwuchsführungskräfte an Berufskollegs - Kundisch, Heike; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Multiprofessionelle Teamarbeit - Notwendigkeit und (schleichende) Veränderung von Berufskollegs - Kückmann, Marie-Ann; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Auf dem Wege zur Qualität in der Ausbildungsvorbereitung - Einblicke in Prozesse zur Entwicklung und Implementation innovativer Konzepte - Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionn aus dem Forschungs- und Entwicklungsprojekt InBig)

Entwicklung von Berufskollegs - Handlungsfelder, Herausforderungen und Unterstützungsbedarf von Nachwuchsführungskräften in der Beruflichen Bildung - Kremer, H.-Hugo; Kundisch, Heike; Schreiner, K. (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsarbeit. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Connecting In-Body Nano Communication with Body Area Networks: Challenges and Opportunities of the Internet of Nano Things - Dressler, Falko; Fischer, Stefan (Elsevier Nano Communication Networks)
Nano-communication is considered to become a major building block for many novel applications in the health care and fitness sector. Given the recent developments in the scope of nano machinery, coordination and control of these devices becomes the critical challenge to be solved. In-Body Nano-Communication based on either molecular, acoustic, or RF radio communication in the terahertz band supports the exchange of messages between these in-body devices. Yet, the control and communication with external units is not yet fully understood. In this paper, we investigate the challenges and opportunities of connecting Body Area Networks and other external gateways with in-body nano-devices, paving the road towards more scalable and efficient Internet of Nano Things (IoNT) systems. We derive a novel network architecture supporting the resulting requirements and, most importantly, investigate options for the simulation based performance evaluation of such novel concepts. Our study is concluded by a first look at the resulting security issues considering the high impact of potential misuse of the communication links.

Towards Communication Strategies for Platooning: Simulative and Experimental Evaluation - Segata, Michele; Bloessl, Bastian; Joerer, Stefan; Sommer, Christoph; Gerla, Mario; Lo Cigno, Renato; Dressler, Falko (IEEE Transactions on Vehicular Technology)
Platooning, the idea of cars autonomously following their leaders to form a road train, has huge potentials to improve traffic flow efficiency and, most importantly, road traffic safety. Wireless communication is a fundamental building block - it is needed to manage and to maintain the platoons. To keep the system stable, strict constraints in terms of update frequency and communication reliability must be met. We investigate different communication strategies by explicitly taking into account the requirements of the controller, exploiting synchronized communication slots as well as transmit power adaptation. As a baseline, we compared the proposed approaches to two state of the art adaptive beaconing protocols that have been designed for cooperative awareness applications, namely ETSI DCC and DynB. Our simulation models have been parameterized and validated by means of real-world experiments. Our results demonstrate that the combination of synchronized communication slots with transmit power adaptation is perfectly suited for cooperative driving applications, even in very crowded freeway scenarios.

Erleben Schulischer Wirklichkeit - Schulische Langeweile aus Sicht von Jugendlichen an Berufskollegs - Dirksmeier, V.; Gonsior, R.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kein Ende...vor dem Anfang einer weiteren Professionalisierung der Bildungsarbeit - Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Interference of surface plasmons and Smith-Purcell emission probed by angle-resolved cathodoluminescence spectroscopy - Yamamoto, Naoki; Javier García de Abajo, F.; Myroshnychenko, Viktor (Physical Review B)
We investigate the interplay between geometrical lattice resonances and surface plasmons mediating the emission of Smith-Purcell visible light via angle-resolved cathodoluminescence spectroscopy. We observe strong modulations in the dispersion curves of Smith-Purcell radiation (SPR) when they intersect the surface plasmons of silver gratings using a 200-kV transmission electron microscope. The decay of the plasmons away from the grating is directly probed by controlling the electron-beam position relative to the sample surface with nanometer precision. Our measurements are in excellent agreement with numerical simulations, clearly revealing the presence of characteristic Fano profiles resulting from the interference of the light continuum and the discrete plasmon states for each direction of emission. The intensity anomaly in the SPR emission pattern can be well explained from the geometrical consideration of the intersections between the dispersion planes of the SPR and surface plasmon polariton (SPP). A strong and directional SPR beam can be realized under the condition that the SPR dispersion plane comes in contact with the band edge of the SPP dispersion plane.

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari

Pädagogische Hochschulentwicklung: Von der Programmatik zur Implementierung - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
Der Sammelband befasst sich mit einem umfassenden Ansatz zur Verbesserung der Qualität von Lehre und Studium. Mit dem Konzept der pädagogischen Hochschulentwicklung plädieren die AutorInnen dafür, bei der Umsetzung von Veränderungsprojekten die verschiedenen Ebenen der Hochschule zu verschränken. Zum Beispiel sollten Initiativen, die eine Lehrveranstaltung betreffen, idealerweise die (Aus )Wirkungen auf den Ebenen der Studienprogramme und der Organisation berücksichtigen und aktiv gestalten. Die einzelnen Beiträge stellen beispielhafte Initiativen aus unterschiedlichen Disziplinen und Hochschulformen dar und illustrieren, wie die genannten Ebenen in der praktischen Umsetzung verzahnt werden können.

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari
Starting with this issue, the ZFHE will publish one English-speaking edition per year on a topic of international interest, in order to disseminate German-language research results beyond our borders and to encourage discussion in an international context. This first English-language edition focuses on the experiences and the academic socialization of first-year university students. The articles offer both diagnoses and differentiations in terms of different types of first-year students, as well as highlighting their experiences and development during their introduction to the academic environment and examining connections between their academic development and the existing educational environment.

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

How Do They Find Their Place? A Longitudinal Study of Management Students' Attitudes and Motivations During Their First Year at Business School - Jenert, Tobias; Brahm, Taiga
The first year of studying has been extensively researched applying different theoretical lenses to better understand the transition into Higher Education (HE). It is of particular interest to investigate how students deal with frictions between themselves as individuals and what they perceive to be dominant features of the first-year culture of their studies. To tackle this question, a qualitative longitudinal study was conducted. Based on a sociocultural understanding of attitudes and motivations, its aim was to closely follow a relatively small but highly diverse sample of students throughout their first year at a business school in order to develop an in-depth understanding of each individual’s motivational and attitudinal development.
Keywords: Enculturation; first-year students; beginning students; retention; drop-out

The crucial first year: Students’ motivation at a Swiss Business School--a longitudinal study - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Academy of Management Proceedings)
Despite students’ motivation being considered a strong predictor of performance, the development of motivation of business school students has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. This is surprising, as the transition from school to university is a crucial phase in the academic career and can be overwhelming for some students. The present study addresses this research gap and examines the development of economics and management students’ study motivation. The longitudinal study included four waves of data collected throughout the first year using quantitative surveys. Regarding students’ development over time, the analysis showed a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline

Zwischen Individuum, Institution und Disziplin: Methodologische Überlegungen zur Erfassung von Lernkulturen an Hochschule - Jenert, Tobias; Reinmann, Gabi (Dokumentation der Jahrestagung der Sektion Erwachsenenbildung der DGfE)
Keywords: Methodologie; Lernforschung; hochschuldidaktische Forschung; Higher Education

Zwischen" netten" Tools und" Überdidaktisierung": Neue Medien in der Hochschuldidaktik - Wagner, Dietrich; Jenert, Tobias
Auswertung einer Befragung unter Studierenden zu der Frage welche Elemente eine Lehrveranstaltung innovativ machen und welche Rolle die neuen Medien dabei spielen. Digitale Medien begegnen uns in der Hochschule immer wieder. Häufig handelt es sich um neue Werkzeuge oder Trends (Klicker, MOOCs, Web 2.0), die einerseits potenzialreich und spannend erscheinen, deren didaktische Verwertbarkeit sich aber nicht auf den ersten Blick erschließt. Oft folgt nach einer euphorischen Erprobung schnell die Ernüchterung, wenn festgestellt wird, dass sich durch die digitalen Technologien allein kein erhöhter Lernerfolg ergibt und auch die Studierenden keine nachhaltigen Motivationsschübe erfahren. Aus der Hochschuldidaktik hört man häufig und berechtigterweise kritische Stimmen, welche die Einbettung digitaler Medien in sorgfältig geplante didaktische Arrangements betonen. Es stellt sich die Frage, inwieweit damit die Kreativität und der Entdeckergeist von Lehrenden und Studierenden eingeschränkt werden. Wir wollen im Disq-Space der Frage nachgehen, wie die Hochschuldidaktik auf neue digitale Trends reagieren und dabei einen Mittelweg zwischen "kreativem Ausprobieren" und pädagogisch-didaktischer Rationalität einschlagen kann. Zunächst werden die Ergebnisse einer aktuellen Umfrage an der Universität St. Gallen zu den Vorstellungen Studierender zu innovativer Lehre vorgestellt. Nach einer Öffnung des Raums für gute sowie schlechte Erfahrungen und Bespiele von Seiten der Teilnehmenden soll diskutiert werden, welche personellen, didaktischen und organisatorischen Voraussetzungen erfüllt sein müssen, damit Digitalisierung die Kompetenzentwicklung der Studierenden unterstützt. Die Ergebnisse der Diskussionsrunde werden im Blog des Teams Hochschulentwicklung zur Verfügung gestellt. Es wird angestrebt, diese damit einer breiteren Öffentlichkeit zugänglich zu machen.
Keywords: Neue Medien; Hochschuldidaktik; Studierende; Innovation in der Lehre

On the iterative plug-in algorithm for estimating diurnal patterns of financial trade durations - Feng, Yuanhua; Forstinger, Sarah; Peitz, Christian (Journal of Statistical Computation and Simulation)

Forecasting financial market activity using a semiparametric fractionally integrated Log-ACD - Feng, Yuanhua; Zhou, Chen (International Journal of Forecasting)

Empirical Economic and Financial Research - Theory, Methods and Practice

Introduction - Beran, Jan; Feng, Yuanhua; Hebbel, Hartmut (Empirical Economic and Financial Research)

An iterative plug-in algorithm for realized kernels - Feng, Yuanhua; Zhou, Chen

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups?, - Ortmann, Regina
Formulary apportionment is an intensively debated mechanism for allocating tax base within multinational groups. Systems under which the formula is identical in all jurisdictions and systems under which jurisdictions can determine the weights on the formula factors individually can be observed. The latter systems produce uncertainty about the overall tax-liable share of the future group tax base. Counter-intuitively, I identify scenarios under which increased uncertainty leads to higher expected future group income. My results provide helpful insights for firms and policy makers debating the specific design of a formulary apportionment system.

Formula Apportionment or Separate Accounting? Tax-Induced Distortions of Multinationals' Locational Investment Decisions - Ortmann, Regina; Pummerer, Erich

Entscheidungskalküle US-amerikanischer Unternehmen bei Tax Inversions. What Drives the Decision of U.S. Firms to Expatriate? - Oßwald, Benjamin; Sureth-Sloane, Caren (Steuer und Wirtschaft International)

Investment Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren

Hold or Sell? How Capital Gains Taxation Affects Holding Decisions - Hegemann, Annika; Kunoth, Angela; Rupp, Kristina; Sureth-Sloane, Caren

The Effect of Taxes on Corporate Financing Decision - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren

BI-Service-orientierte Leistungsverrechnung - Grytz, Raphael; Krohn-Grimberghe, Artus (Handbuch Business Intelligence. Potenziale, Strategien, Best Practices)

Fast Fuzzy Pattern Tree Learning for Classification - Senge, Robin; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Active zinc-blende III–nitride photonic structures on silicon - Sergent, Sylvain; Kako, Satoshi; Bürger, Matthias; Blumenthal, Sarah; Iwamoto, Satoshi; As, Donat Josef; Arakawa, Yasuhiko (Applied Physics Express)

Temperature dependence of the electron Landé g-factor in cubic GaN - Buß, J. H.; Schupp, T.; As, Donat Josef; Hägele, D.; Rudolph, J. (Journal of Applied Physics)

Strain dependent electron spin dynamics in bulk cubic GaN - Schaefer, A.; Buß, J. H.; Schupp, T.; Zado, A.; As, Donat Josef; Hägele, D.; Rudolph, J. (Journal of Applied Physics)

Managing the bright and dark sides of status endowment in hierarchical loyalty programs - Eggert, Andreas; Steinhoff, Lena; Garnefeld, Ina (Journal of Service Research)

How sales strategy translates into performance: The role of salesperson customer orientation and value-based selling - Terho, Harri; Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang (Industrial Marketing Management)

Heading for new shores: Do service and hybrid innovations outperform product innovations in industrial companies? - Eggert, Andreas; Thiesbrummel, Christoph; Deutscher, Christian (Industrial Marketing Management)

"...and they are really lying: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment" - Djawadi, Behnud Mir; Fahr, René (Journal of Economic Psychology)

Bank funding stability, pricing strategies and the guidance of depositors - Schlueter, Tobias; Sievers, Sönke; Hartmann-Wendels, Thomas (Journal of Banking & Finance (VHB-JOURQUAL 3 Ranking A))
Banks face a 'behavioralization' of their balance sheets since deposit funding increasingly consists of non-maturing deposits with uncertain cash flows exposing banks to asset liability (ALM) risk. Thus, this study examines the behavior of banks’ retail customers regarding non-maturing deposits. Our unique sample comprises the contract and cash flow data for 2.2 million individual contracts from 1991 to 2010. We find that contractual rewards, i.e., qualified interest payments, and government subsidies, effectively stabilize saving behavior and thus bank funding. The probability of an early deposit withdrawal decreases by approximately 40%, and cash flow volatility drops by about 25%. Our findings provide important insights for banks using pricing incentives to steer desired saving patterns for their non-maturing deposit portfolios. Finally, these results are informative regarding the bank liquidity regulations (Basel III) concerning the stability of deposits and the minimum requirements for risk management (European Commission DIRECTIVE 2006/48/EC).
Keywords: retail saving behavior; non-maturing deposits; deposit funding; contractual rewards; interest rate bonus; saving persistence; cash flow volatility

Robust Equilibria in Location Games - Buechel, Berno; Röhl, Nils (European Journal of Operational Research)
In the framework of spatial competition, two or more players strategically choose a locationin order to attract consumers. It is assumed standardly that consumers with the same favorite location fully agree on the ranking of all possible locations. To investigate the necessity of this questionable and restrictive assumption, we model heterogeneity in consumers’ distance perceptions by individual edge lengths of a given graph. A proﬁle of location choices is called a “robust equilibrium” if it is a Nash equilibrium in several games which diﬀer only by the consumers’ perceptions of distances. For a ﬁnite number of players and any distribution of consumers, we provide a full characterization of all robust equilibria and derive structural conditions for their existence. Furthermore, we discuss whether the classical observations of minimal diﬀerentiation and ineﬃciency are robust phenomena. Thereby, we ﬁnd strong support for an old conjecture that in equilibrium ﬁrms form local clusters.

Wertbasiertes Verkaufen auf Industriegütermärkten - Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang; Terho, Harri (Handbuch Business-to-Business-Marketing)

Public good provision in blended groups of partners and strangers - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Economics Letters)

Behavioral spillovers from freeriding in multilevel interactions - Thommes, Kirsten; Vyrastekova, Jana; Akkerman, Agnes (Journal of Behavioral and Experimental Economics)

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences

Ultrafast carrier dynamics and resonant inter-miniband nonlinearity of a cubic GaN/AlN superlattice - Jostmeier, Thorben; Wecker, Tobias; Reuter, Dirk; As, Donat Josef; Betz, Markus (Applied Physics Letters)

Nuclear spin polarization in the electron spin-flip Raman scattering of singly charged (In,Ga)As/GaAs quantum dots - Debus, J.; Kudlacik, D.; Sapega, V. F.; Dunker, D.; Bohn, P.; Paßmann, F.; Braukmann, D.; Rautert, J.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Transform-limited single photons from a single quantum dot - Kuhlmann, Andreas V.; Prechtel, Jonathan H.; Houel, Julien; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Nature Communications)

Influence of Post-Implantation Annealing Parameters on the Focused Ion Beam Directed Nucleation of InAs Quantum Dots - Mehta, M.; Reuter, Dirk; Kamruddin, M.; Tyagi, A. K.; Wieck, A. D. (Nano)

Fabrication and characterisation of gallium arsenide ambipolar quantum point contacts - Chen, J. C. H.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Trunov, K.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)

Extending the spectral range of CdSe/ZnSe quantum wells by strain engineering - Finke, A.; Ruth, M.; Scholz, S.; Ludwig, A.; Wieck, A. D.; Reuter, Dirk; Pawlis, A. (Physical Review B)

Skalieren von großen agilen Projekten mit verteilten Backlogs - Güldali, Baris; Fazal-Baqaie, Masud (OBJEKTspektrum (Online Themenspecials))

Agile Entwicklung mit On- und Offshore-Partnern – Methodenverbesserung in der Praxis - Fazal-Baqaie, Masud; Sauer, Stefan; Heuft, Torsten (WI-MAW-Rundbrief)

Towards a Framework for the Modular Construction of Situation-Specific Software Transformation Methods - Grieger, Marvin; Fazal-Baqaie, Masud (Softwaretechnik-Trends, Proceedings of the 17th Workshop Software-Reengineering (WSRE))

Modellbasiertes Testen bei der Entwicklung einer IKT-Infrastruktur für Elektromobilität - Güldali, Baris; Rose, Mirko; Teetz, Alexander; Flake, Stephan; Rust, Carsten

On-the-Fly Computing: Automatic Service Discovery and Composition in Heterogeneous Domains - Huma, Zille; Gerth, Christian; Engels, Gregor (Computer Science - Research and Development)

On Network Application representation and controller independence in {SDN - A. Aranda-Gutierrez, Pedro; Karl, Holger; Rojas, Elisa; Leckey, Alec (2015 European Conference on Networks and Communications, EuCNC 2015, Paris, France, June 29 - July 2, 2015)

Error characterization of multi-access point WSNs in an aircraft cabin - Blanckenstein, Johannes; Nardin, Cristina; Klaue, Jirka; Karl, Holger (IEEE International Conference on Communication, ICC 2015, London, United Kingdom, June 8-12, 2015, Workshop Proceedings)

Topology model to generate realistic latency for simulations - Schwabe, Arne; Karl, Holger (2015 IEEE International Conference on Communications, ICC 2015, London, United Kingdom, June 8-12, 2015)

Anticipatory Download Scheduling in Wireless Video Streaming with Uncertain Data Rate Prediction - Dräxler, Martin; Blobel, Johannes; Karl, Holger (8th IFIP Wireless and Mobile Networking Conference, WMNC 2015, Munich, Germany, October 5-7, 2015)

Extending Hadoop's Yarn Scheduler Load Simulator with a highly realistic network & traffic model - Wette, Philip; Schwabe, Arne; Splietker, Malte; Karl, Holger (Proceedings of the 1st IEEE Conference on Network Softwarization, NetSoft 2015, London, United Kingdom, April 13-17, 2015)

Kurzportrait zum Standortkonzept des Berufskollegs West der Stadt Essen - Frehe, Petra; Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Flexible reassignment of flow processing-aware controllers in future wireless networks - Auroux, Sébastien; Karl, Holger (26th IEEE Annual International Symposium on Personal, Indoor, and Mobile Radio Communications, PIMRC 2015, Hong Kong, China, August 30 - September 2, 2015)

Efficient flow processing-aware controller placement in future wireless networks - Auroux, Sébastien; Karl, Holger (2015 IEEE Wireless Communications and Networking Conference, WCNC 2015, New Orleans, LA, USA, March 9-12, 2015)

Specification of Complex Structures in Distributed Service Function Chaining Using a YANG Data Model - Dräxler, Sevil; Karl, Holger (CoRR)

Dynamic Backhaul Network Configuration in SDN-based Cloud RANs - Dräxler, Martin; Karl, Holger (CoRR)

Pipelines for Ad-hoc Large-scale Text Mining - Wachsmuth, Henning
Today's web search and big data analytics applications aim to address information needs~(typically given in the form of search queries) ad-hoc on large numbers of texts. In order to directly return relevant information instead of only returning potentially relevant texts, these applications have begun to employ text mining. The term text mining covers tasks that deal with the inference of structured high-quality information from collections and streams of unstructured input texts. Text mining requires task-specific text analysis processes that may consist of several interdependent steps. These processes are realized with sequences of algorithms from information extraction, text classification, and natural language processing. However, the use of such text analysis pipelines is still restricted to addressing a few predefined information needs. We argue that the reasons behind are three-fold: First, text analysis pipelines are usually made manually in respect of the given information need and input texts, because their design requires expert knowledge about the algorithms to be employed. When information needs have to be addressed that are unknown beforehand, text mining hence cannot be performed ad-hoc. Second, text analysis pipelines tend to be inefficient in terms of run-time, because their execution often includes analyzing texts with computationally expensive algorithms. When information needs have to be addressed ad-hoc, text mining hence cannot be performed in the large. And third, text analysis pipelines tend not to robustly achieve high effectiveness on all texts, because their results are often inferred by algorithms that rely on domain-dependent features of texts. Hence, text mining currently cannot guarantee to infer high-quality information. In this thesis, we contribute to the question of how to address information needs from text mining ad-hoc in an efficient and domain-robust manner. We observe that knowledge about a text analysis process and information obtained within the process help to improve the design, the execution, and the results of the pipeline that realizes the process. To this end, we apply different techniques from classical and statistical artificial intelligence. In particular, we first develop knowledge-based approaches for an ad-hoc pipeline construction and for an optimal execution of a pipeline on its input. Then, we show theoretically and practically how to optimize and adapt the schedule of the algorithms in a pipeline based on information in the analyzed input texts in order to maximize execution efficiency. Finally, we learn patterns in the argumentation structures of texts statistically that remain strongly invariant across domains and that, thereby, allow for more robust analysis results in a restricted set of tasks. We formally analyze all developed approaches and we implement them as open-source software applications. Based on these applications, we evaluate the approaches on established and on newly created collections of texts for scientifically and industrially important text analysis tasks, such as financial event extraction and fine-grained sentiment analysis. Our findings show that text analysis pipelines can be designed automatically, which process only portions of text that are relevant for the information need at hand. Through scheduling, the run-time efficiency of pipelines can be improved by up to more than one order of magnitude while maintaining effectiveness. Moreover, we provide evidence that a pipeline's domain robustness substantially benefits from focusing on argumentation structure in tasks like sentiment analysis. We conclude that our approaches denote essential building blocks of enabling ad-hoc large-scale text mining in web search and big data analytics applications.

Challenges for Model-Integrating Components - Derakhshanmanesh , Mahdi; Ebert , Jürgen; Grieger, Marvin (Proceedings of the 2nd International Workshop on Model-Driven Engineering for Component-Based Software Systems co-located with ACM/IEEE 18th International Conference on Model Driven Engineering Languages & Systems (MoDELS 2015))

On Enabling Technologies for Longevity in Software - Derakhshanmanesh , Mahdi; Grieger, Marvin (Gemeinsamer Tagungsband der Workshops der Tagung Software Engineering 2015)

On the Need for Transactional Models@Run.Time - Derakhshanmanesh , Mahdi; Grieger , Marvin; Ebert, Jürgen (Proceedings of the 10th Workshop on Models@run.time co-located with 18th International Conference on Model Driven Engineering Languages and Systems (MODELS 2015))

Perceived Autonomy in the First Semester of Mathematics Studies - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the Ninth Congress of the European Society for Research in Mathematics Education)

Initiative Bottom-Up-Nachtreffen zum Doktorandenkolloquium der GDM - Braun, Eileen Angélique; Liebendörfer, Michael; Schorcht, Sebastian (Mitteilungen der Gesellschaft für Didaktik der Mathematik)

Multiobjective Optimization of the Flow Around a Cylinder Using Model Order Reduction - Peitz, Sebastian; Dellnitz, Michael (PAMM)
n this article an efficient numerical method to solve multiobjective optimization problems for fluid flow governed by the Navier Stokes equations is presented. In order to decrease the computational effort, a reduced order model is introduced using Proper Orthogonal Decomposition and a corresponding Galerkin Projection. A global, derivative free multiobjective optimization algorithm is applied to compute the Pareto set (i.e. the set of optimal compromises) for the concurrent objectives minimization of flow field fluctuations and control cost. The method is illustrated for a 2D flow around a cylinder at Re = 100.

„Career Planning for dynamic Economies" – Individualisierung und Neue Medien als Anknüpfungspunkt für berufliche Orientierung im Rahmen des EU geförderten Projekts SELFIE - Beutner, Marc; Rose, S (Wirtschaft und Erziehung)